PERHITUNGAN MANUAL DENGAN MENGGUNAKAN METODA SAW (Simple Additive Weighting) - Hamid Al Jufri (LPPM Universitas Bina Bangsa, 2022)
Decision Support System Selection of the location of an educational institution using the SAW (Simple Additive Weighting) method is a system that can determine the decision making to choose an educational institution based on the criteria and alternatives that have been determined. There are various factors that must be considered when choosing an educational institution. The determination of an educational institution must go through proper analysis and calculations so that an educational institution can be determined in accordance with what is seen from various aspects. In determining the selection of educational institutions, must have several criteria that have been set. These criteria include facilities, price, and location. The above problem can be solved by using the SAW (Simple Additive Weighting) method, because this method is able to provide decision support for multi-criteria and multi-alternative problems. With a Decision Support System that uses the SAW (Simple Additive Weighting) method, it can speed up and make it easier to make decisions to choose an educational institution in accordance with predetermined criteria.